Approach for integrated modular avionics reconfiguration modelling and reliability analysis based on AADL. Issue 1 (1st February 2016) - Zhang, Quan; Wang, Shihai; Liu, Bin
Abstract : To optimise the configuration and reconfiguration strategies in integrated modular avionics (IMA), modelling and evaluating the reliability of the reconfigurable IMA system have drawn great attention from system engineers and designers. Currently most researches regard each configuration as a single system state, but the detailed system architecture under each configuration or the events that trigger the reconfiguration behaviour are not involved. In this study, a modelling method is proposed for these complex processes of the IMA reconfiguration. It employs architecture analysis and design language (AADL) along with its Error Model Annex, ARINC653 Annex, and mode transition mechanisms to model the correlated component error state transitions, system configuration architectures, and reconfiguration behaviours. Based on the proposed AADL modelling approach, these model information is extracted purposefully to establish computable models. Then a reliability analysis approach is proposed which is able to result in various reliability attributions, such as component reliability, configuration reliability under the software architecture, single task reliability, and multi‐tasking reliability. These evaluation processes take into account both of the fault isolation reconfiguration and task mode reconfiguration for the first time. Finally, the case study is involved, which demonstrates the feasibility of the analysis approach for IMA based on an AADL model.